Analisis Kegiatan Dan Problema Lansia Di UPTD Pelayanan Sosial Lanjut Usia Binjai Dinas Sosial Provsu - Ramadhan Lubis (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2025)
This study aims to observe various activities and identify the problems faced by the elderly residents at the UPTD Social Service Center for the Elderly in Binjai, under the Social Service Office of North Sumatra Province. The research employed a qualitative approach using in-depth interviews and direct observation with the elderly residents and social workers. Interviews were conducted with several elderly participants and staff members to obtain an overview of their daily activities, as well as their social, psychological, and health-related needs. Observations were carried out to directly examine the dynamics of activities and social interactions within the institution. The findings indicate that the elderly at the UPTD participate in various activities such as religious practices, light handicrafts, mild physical exercises, and social recreation, all of which aim to improve their quality of life and sense of togetherness. However, several issues were identified, including limited activity facilities, chronic health problems, feelings of loneliness, and a lack of emotional support from families. Based on the results of interviews and observations, it can be concluded that although the social services have been implemented quite well, there is still a need for improvement in psychosocial assistance, diversification of productive activities, and better health facilities.